Painful Past in the Service of Israeli Jewish-Arab Dialogue: The Work of the Center for Humanistic Education at the Ghetto Fighters House in Israel (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
The Centre for Humanistic Education (CHE) within the museum of Ghetto Fighters’ House (GFH) in Israel, engages high-school students and teachers from the Arab and Jewish sectors in an examination of connections between the Holocaust; personal and social morals; and implications for present Israeli society.